2019
DOI: 10.1001/jamapsychiatry.2019.2325
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Time Spent Using Social Media and Internalizing and Externalizing Problems Among US Youth

Abstract: IMPORTANCE Social media use may be a risk factor for mental health problems in adolescents. However, few longitudinal studies have investigated this association, and none have quantified the proportion of mental health problems among adolescents attributable to social media use.OBJECTIVE To assess whether time spent using social media per day is prospectively associated with internalizing and externalizing problems among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
152
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 279 publications
(201 citation statements)
references
References 37 publications
10
152
1
7
Order By: Relevance
“…Research on social media and adolescent mental health has proliferated in recent years, with many studies exploring whether more frequent use of social media is associated with various mental health concerns, including depression [11], body image concerns and disordered eating [12], and externalizing problems [13]. In general, findings from these studies have been mixed, with many revealing a small but significant negative effect of social media use on mental health.…”
Section: Understanding the Impact Of Social Media On Youth Mental Healthmentioning
confidence: 99%
“…Research on social media and adolescent mental health has proliferated in recent years, with many studies exploring whether more frequent use of social media is associated with various mental health concerns, including depression [11], body image concerns and disordered eating [12], and externalizing problems [13]. In general, findings from these studies have been mixed, with many revealing a small but significant negative effect of social media use on mental health.…”
Section: Understanding the Impact Of Social Media On Youth Mental Healthmentioning
confidence: 99%
“…Eine wichtige erste Beantwortung der Frage, ob eine intensive Nutzung von Social Media auch ursächlich zum Auftreten psychischer Probleme beitragen kann, liefert eine methodisch ausgewogene Studie aus den USA, die unlängst veröffentlicht wurde [4]. Die Autoren erhoben an einer repräsentativen Stichprobe von 6596 Jugendlichen im Alter zwischen 12 und 17 Jahren mittels Fragebogen einerseits die täglich mit der Nutzung von Social Media zugebrachte Zeit und zusätzlich das Ausmaß an erlebten internalisierenden und externalisierenden Symptomen.…”
Section: Zusammenhänge Zwischen Social Media-nutzung Und Psychischer unclassified
“…Social networking and traditional communication, the two activities that might be subsumed under the term "communication", showed associations with conduct problems. This nding is surprising given that previous studies suggest associations with internalizing rather than externalizing behavior [24]. A possible explanation is that adolescents with conduct problems might show aggressive behavior not only in real but also in online social interactions, e.g., via cyberbullying [26].…”
Section: Associations Between Media Usage and Behavioral Strengths Anmentioning
confidence: 74%
“…With respect to the use of social networking sites, previous studies showed associations with more psychological distress and poorer mental health [21,22], especially more internalizing behavioral problems and depressive symptoms [23,24]. However, some studies also observed associations with externalizing problems and violence [25,26].…”
Section: Introductionmentioning
confidence: 99%